Ketersisihan Pedagang Arab di Empat Wilayah Jakarta Tahun 1960-1990 - Zeffry, Zeffry (UI Scholars Hub, 2004)
The purpose of this research is to analize the various factors of the isolation of Arabic merchant counterparts in thirty year period, 1960-1990, that is based on filed research in four areas in Jakarta. The research is a contribution to developing three core diciplines, such as history, sociology, and anthropology especialy that is related to the problem of social change that happens in urban society and more specifically one that concern a certain ethnic community in the society. The research shows that the phenomenon of social change that happen in Jakarta, in a certain period, may be compared with other similar phenomenon of social change in other cities. This research uses a qualitative model. The social change that is endured by the Arabic ethnic does not represent a single social phenomenon, but it is connected directly or indirectly with other factors. Some of the reason of isolation are the incoming another merchant from different place who open new store in the Arabic area beside the lack of motivation on the part of the young Arabic store owner to continu businesses initiated by their parent. At the same time, distribute particular product or produce certain merchandise that have never been done by the Arabic merchant, in iddition to that, the Arabic merchants move their businesse to other kind of trade.